Representasi Konflik Kelas Sosial dalam Film Parasite Ditinjau dari Perspektif Ralf Dahrendorf - Sya'adah, Ummu (LoroNG: Media Pengkajian Sosial Budaya, 2025)
This research discusses social class conflicts that occur in the film Parasite and social change using Ralf Dahrendorf's theory. The data used are dialog quotes and scenes that illustrate class conflict and social change. This type of research uses descriptive qualitative research methods. The data collection used is the method of listening and recording while the analysis method used is the content analysis method.